Hypertensive Diet Compliance With Blood Pressure For The Elderly In Muara Besar Village, The Working Area Of The Ogodeide Health Center - Salmia; Atik Setiawan Wahyuningsih; Eva Agustina (Universitas STRADA Indonesia, 2020)
Hypertension is a problem that is difficult to control because hypertensive patients rarely feel a symptom that the sufferer does not realize until they experience complications in vital organs such as the heart, brain and kidneys. Prevention of hypertension can be done by continuing a hypertensive diet to prevent further severe impacts. Objective: To find out if there is Dietary Compliance with Hypertension with Blood Pressure in the Elderly in Muara Besar Village, Ogodeide Health Center Working Area, Tolitoli Regency. The design used in the study was observational The population was All Elderly Hypertension. The sample size was 37 respondents using the Simple Random sampling technique. The Independent Variable of the study was dietary adherence. The dependent variable is Blood pressure. The data was collected using a questionnaire, then the data was analyzed using the Spearman rho test , with a significance level of α ≤ 0.05. The results of the study were obtained that p=0.021 with a=0.05, which means that H0 is rejected and H1 is accepted so that it can be interpreted that there is a relationship between hypertensive dietary compliance with blood pressure reduction in the elderly in Muara Besar Village, Ogodeide Health Center Working Area, Tolitoli Regency, with a correlation coefficient of 0.379 which means that there is a strong relationship. Hypertensive patients who are regular in their diet will increase the stability of blood pressure through the relaxation mechanism of blood vessels located in the vasomotor center which results in vasodilation activity so that blood pressure becomes stable